Local dose enhancement of proton therapy by ceramic oxide nanoparticles investigated with Geant4 simulations. Issue 12 (December 2016) - McKinnon, Sally; Guatelli, Susanna; Incerti, Sebastien; Ivanchenko, Vladimir; Konstantinov, Konstantin; Corde, Stéphanie; Lerch, Michael; Tehei, Moeava; Rosenfeld, Anatoly
Highlights: Study of the dose enhancement by the novel nanoparticles (NPs) Ta2 O5 and CeO2 . Study of the dose enhancement in protontherapy. Dose enhancement produced by an increased number of δ-electrons in the NPs. The dose enhancement is ∼15% for the ceramic NPs compared to ∼25% for gold. Abstract: Nanoparticles (NPs) have been shown to enhance X-ray radiotherapy and proton therapy of cancer. The effectiveness of radiation damage is enhanced in the presence of high atomic number (high-Z) NPs due to increased production of low energy, higher linear energy transfer (LET) secondary electrons when NPs are selectively internalized by tumour cells. This work quantifies the local dose enhancement produced by the high-Z ceramic oxide NPs Ta2 O5 and CeO2, in the target tumour, for the first time in proton therapy, by means of Geant4 simulations. The dose enhancement produced by the ceramic oxides is compared against gold NPs. The energy deposition on a nanoscale around a single nanoparticle of 100 nm diameter is investigated using the Geant4-DNA extension to model particle interactions in the water medium. Enhancement of energy deposition in nano-sized shells of water, local to the NP boundary, ranging between 14% and 27% was observed for proton energies of 5 MeV and 50 MeV, depending on the NP material. Enhancement of electron production and energy deposition can be correlated to the direct DNA damage mechanism if the NP is in close proximity to the nucleus.